Effects of magnetic and non‐magnetic doping on the vortex lattice in MgB2. Issue 4 (15th June 2022) - Louden, Elizabeth R.; Manni, Soham; Zandt, Judah E. Van; Leishman, Allan W. D.; Taufour, Valentin; Bud'ko, Sergey L.; DeBeer-Schmitt, Lisa; Honecker, Dirk; Dewhurst, Charles D.; Canfield, Paul C.; Eskildsen, Morten R.
Abstract : The vortex lattice phase diagram, order and transition kinetics in superconducting MgB2 doped with either manganese or carbon were studied using small‐angle neutron scattering. Abstract : Small‐angle neutron scattering has been used to study the vortex lattice in superconducting MgB2 doped with either manganese or carbon to achieve a similar suppression of the critical temperature. Measurements were performed with the magnetic field applied along the c axis, where the vortex lattice in pure MgB2 is known to undergo a field‐ and temperature‐driven 30° rotation transition. For Mn doping, the vortex lattice phase diagram remains qualitatively similar to that of pure MgB2, indicating only a modest effect on the vortex–vortex interaction. In contrast, the vortex lattice rotation transition is completely suppressed in the C‐doped case, probably due to a change in the electronic structure which affects the two‐band/two‐gap nature of superconductivity in MgB2 . The vortex lattice longitudinal correlation length shows the opposite behavior, remaining roughly unchanged between pure and C‐doped MgB2 while it is significantly reduced in the Mn‐doped case. However, the extensive vortex lattice metastability and related activated behavior, observed in conjunction with the vortex lattice transition in pure MgB2, are also seen in the Mn‐doped sample. This shows that the vortex lattice disordering is not associated with a substantially increased vortex pinning.